Can Obstetric Risk Factors Predict Fetal Acidaemia at Birth? A Retrospective Case-Control Study. (2nd September 2018) - Kapaya, Habiba; Williams, Roslyn; Elton, Grace; Anumba, Dilly
Abstract : Background . Despite major advances in perinatal medicine, intrapartum asphyxia remains a leading and potentially preventable cause of perinatal mortality and long-term morbidity. The umbilical cord pH is considered an essential criteria for the diagnosis of acute intrapartum hypoxic events. The purpose of this study was to evaluate whether obstetric risk factors are associated with fetal acidaemia at delivery. Methodology . In a case-control study, 294 women with term singleton pregnancies complicated by an umbilical artery cord pH < 7.20 at birth were individually matched by controls with umbilical artery cord pH > 7.20. Groups were compared for differences in maternal, obstetric, and fetal characteristics using logistic regression models presented as odds ratio (OR) with 95% confidence intervals (CI). Results . The study showed pregestational diabetes (PGDM) [OR: 5.31, 95% CI: 1.15- 24.58, P = 0.018], urinary tract infection (UTI) [OR: 3.21, 95% CI: 1.61- 6.43, P < 0.001], and low Apgar scores to be significantly associated with acidaemia, whereas low maternal BMI [OR: 0.19, 95% CI: 0.04-0.87, P = 0.032], pyrexia in labour [OR 0.23; 95% CI 0.12-0.53; P < 0.001], electronic fetal monitoring (EFM) [OR 0.65; 95% CI 0.43-0.99; P = 0.042), and emergency caesarean section [OR 0.42; 95% CI 0.26-0.66; P < 0.001] were found to be protective of acidaemia. Conclusion . Certain obstetric risk factors before and during labour can identify newborns at risk of developing acidaemia. Further research is needed to gain quantitative insight into the predictive capacity of these risks that can inform obstetric clinical management for improved outcomes.